Filogeografia e demografia histórica do gênero Galbalcyrhynchus (Aves, Galbulidae). - Serra, Gabriel (Genética, Conservação e Biologia Evolutiva - GCBEv, 2022)
The Neotropics is one of the world's richest biogeographic regions in fauna/flora and several hypotheses attempt to explain reasons behind this high biodiversity. Several hypotheses suggest that the current patterns of biodiversity within the region are the result of regional geological and climatic history. Among the most studied and discussed geological events are the uplift of the Andes Mountains and the consequent reorganization of the drainage system of the Amazon River. For the present study two species were selected from the Neotropical region: Galbalcyrhynchus leucotis (White-eared Jacamar) and Galbalcyrhynchus purusianus (Purus Jacamar). Galbalcyrhynchus leucotis occurs in the western side of the Brazilian Amazon region and in neighboring countries such as Colombia, Peru and Ecuador. Galbalcyrhynchus purusianus occurs in the southwestern Amazonian region in parts of Acre, Rondônia and in the parts of Peru and Bolivia. The present work aimed to reconstruct the phylogenetic relationship and the demographic history of lineages present in species of the genus Galbalcyrhynchus using mitochondrial genome data. We used mitochondrial genomes obtained from tissue samples of 17 individuals belonging to the genus Galbalcyrhynchus and na sample from the group used as na outgroup. Phylogenetic reconstruction for the genus Galbalcyrhynchus indicated that the two species recognized for this genus are monophyletic and showed low intraspecific structuring among individuals. Haplotype networks indicated low nucleotide diversity between the two species. Analyses of divergence time estimates that the age of diversification between the two species was ~0.75 Ma (confidence interval, HPD ≥ 95 %, 0.57 - 1.01 Ma). For Galbalcyrhynchus leucotis the crown group divergence time was ~ 0.05 Ma (confidence interval, HPD ≥ 95 %, 0.03 - 0.08 Ma) while for Galbalcyrhynchus purusianus the crown group divergence time was ~ 0.076 Ma (confidence interval, HPD ≥ 95 %, 0.05 - 0.11 Ma). The demographic history recovered using the protein coding genes recovered population stability for Galbalcyrhynchus leucotis was ~0.0175 Ma and for Galbalcyrhynchus purusianus was ~0.035 Ma. Therefore, this study of the genus Galbalcyrhynchus with phylogeographic and phylogenetic methods will help us understand how birds restricted to wetland environments respond to landscape change over time.
Keywords: Filogeografia; Estabilidade populacional; Galbalcyrhynchus; Várzeas